Do dogs sense hypoglycaemia?. Issue 7 (27th October 2015) - Weber, K. S.; Roden, M.; Müssig, K.
Abstract: Aims: To summarize the current knowledge on the phenomenon of dogs, both trained and untrained, sensing hypoglycaemia and alerting their owners to it. Methods: Electronic databases were searched for all types of articles reporting on untrained or trained 'diabetes alert' dogs. Articles published up until December 2014 in the English or German language were included. Results: Several case reports and observational studies provide evidence that animals can perform at a level above that attributable to chance, and may reliably detect low diurnal as well as nocturnal hypoglycaemic episodes. Behavioural changes in untrained dogs were reported during 38–100% of hypoglycaemic events experienced by their owners. The sensitivity and specificity of the performance of trained diabetes alert dogs sensing hypoglycaemia ranged from 22 to 100% and 71 to 90%, respectively. Additionally, 75–81% of patients with diabetes who owned a trained dog reported a subsequent improvement in their quality of life. Nevertheless, the available data are limited and heterogeneous because they rely on low patient numbers and survey‐based studies prone to recall bias. Conclusion: Further research is needed to confirm the preliminary data on the reliability and mechanism underlying the dogs' abilities to detect hypoglycaemia, and its impact on patient outcomes. What's new?: Dogs have the innate ability to sense low blood glucose concentrations. Trained diabetes alert dogs may improve the clinical and psychosocial outcomes of patients with diabetes. This short report summarizes the current knowledge on the ability and behaviour of untrained and trained dogs to sense hypoglycaemia, and patient outcomes.